Implementation of Qiyas in E-Commerce Transaction Law - Azama, Irham Muhammad; Firdaus, Firdaus (Yayasan Rahmat Islamiyah, 2025)
The e-commerce transaction system, as a novel phenomenon unknown in early Islam, necessitates the establishment of legal rulings relevant to Sharia principles, one of which is through the method of qiyas. This research aims to examine the relevance of qiyas as a method of istinbat (derivation of Islamic law) in the context of e-commerce transactions, particularly concerning its validity and application. The research employs a qualitative descriptive method with a literature review approach, focusing on classical and contemporary literature discussing the qiyas method and its implementation in e-commerce transaction law. The findings indicate that various forms of e-commerce transactions share legal commonalities (illat) with classical muamalah contracts, thus allowing for analogical deduction (qiyas). The implementation of qiyas in e-commerce transactions encompasses three aspects: 1) transactions in general, 2) the use of internet services, and 3) the payment process.